Novel eIF4A1 inhibitors with anti‐tumor activity in lymphoma - Forum Kayastha; Noah B. Herrington; Bandish Kapadia; Anirban Roychowdhury; Nahid Nanaji; Glen E. Kellogg; Ronald B. Gartenhaus (BMC, 2022)
Abstract Background Deregulated translation initiation is implicated extensively in cancer initiation and progression. It is actively pursued as a viable target that circumvents the dependency on oncogenic signaling, a significant factor in current strategies. Eukaryotic translation initiation factor (eIF) 4A plays an essential role in translation initiation by unwinding the secondary structure of messenger RNA (mRNA) upstream of the start codon, enabling active ribosomal recruitment on the downstream genes. Several natural product molecules with similar scaffolds, such as Rocaglamide A (RocA), targeting eIF4A have been reported in the last decade. However, their clinical utilization is still elusive due to several pharmacological limitations. In this study we identified new eIF4A1 inhibitors and their possible mechanisms. Methods In this report, we conducted a pharmacophore-based virtual screen of RocA complexed with eIF4A and a polypurine RNA strand for novel eIF4A inhibitors from commercially available compounds in the MolPort Database. We performed target-based screening and optimization of active pharmacophores. We assessed the effects of novel compounds on biochemical and cell-based assays for efficacy and mechanistic evaluation. Results We validated three new potent eIF4A inhibitors, RBF197, RBF 203, and RBF 208, which decreased diffuse large B-cell lymphoma (DLBCL) cell viability. Biochemical and cellular studies, molecular docking, and functional assays revealed that thosenovel compounds clamp eIF4A into mRNA in an ATP-independent manner. Moreover, we found that RBF197 and RBF208 significantly depressed eIF4A-dependent oncogene expression as well as the colony formation capacity of DLBCL. Interestingly, exposure of these compounds to non-malignant cells had only minimal impact on their growth and viability. Conclusions Identified compounds suggest a new strategy for designing novel eIF4A inhibitors.